Procena efekata menopauze i gojaznosti na koncentraciju matriptaze-2 i neurokinina B: studija poprečnog preseka: Matriptase-2 and Neurokinin-B in Menopausal Obese - Funda,; SAGSOZ, Nevin (Journal of Medical Biochemistry, 2025)
Background: Matriptase-2 (MT2) is implicated in iron metabolism, obesity, insülin resistance, and glucose homeostasis. Neurokinin B (NKB) plays a crucial role in gonadotropin secretion essential for reproduction. The impact of menopause and obesity on MT2 and NKB concentrations remains an enigma. Therefore, the present study sought to investigate how obesity and menopause affect serum concentrations of MT2 and NKB.Methods: In this cross-sectional study, 120 female volunteers were divided into four groups: menopausal overweight, menopausal obese, menopausal normal weight (control), and reproductive normal weight (control). The participants’ serum levels of MT2, NKB, iron, ferritin, and relevant biochemical parameters were analyzed using the ELISA method. Results: The mean serum concentrations of NKB, MT2, and ferritin were higher in the menopausal overweight and obese groups (p